Pengaruh Harga, Lokasi, dan Kualitas Pelayanan Jasa terhadap Kepuasan Pelanggan Rumah Potong Hewan (RPH) Waylaga Bandar Lampung - Nurheti, Nurheti; Hidayati, Nurul (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
The Development of business word in the era globalization requires perfect performance in every process that is executed by the company. The increasing demand of beef in the community to make all people who have a business that provider faculities and services for its customers. The number of imported cattle that goes to Lampung is required by 10 % cuttins the cuttle in RPH Waylaga accordins to that recommended by the goverment. But in fact, cattle traders still prefer not to cut the in the Waylaga RPH because the reasons is the location not strategies and far from the central of Bandar Lampung.This research uses qualitative approach, and this research also was conducted on April 2017 until finish in Slaughterhouse (RPH) Waylaga Bandar Lampung, the population in this research from all of customers for about 49 people in RPH Waylaga Bandar Lampung. The sample that the research is sampling saturated and the sample set in this research as many as 49 respondent. Based on the result of regression testing between Price, Location, and Quality of Service so that price, Location, and Quality of service have been applied in Cut Out Animal (RPH) Bandar Lampung has influence and positive relation to customer satisfaction while at variable of service quality from partial test. This not has an effect of customer satisfaction in RPH Bandar Lampung.